1998
DOI: 10.2307/3392005
|View full text |Cite
|
Sign up to set email alerts
|

Bulbophyllum involutum Borba, Semir & F. Barros (Orchidaceae), a New Species from the Brazilian "Campos Rupestres"

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 2 publications
0
13
1
7
Order By: Relevance
“…The morphological uniformity observed in the population of B. weddellii in Mucugê points out to the absence of introgression in this species. The situation found in the sampled populations are at odds with the original findings of Borba & Semir (1998a) at Serra do Cipó. These authors found only one individual of B.…”
Section: Resultscontrasting
confidence: 52%
See 4 more Smart Citations
“…The morphological uniformity observed in the population of B. weddellii in Mucugê points out to the absence of introgression in this species. The situation found in the sampled populations are at odds with the original findings of Borba & Semir (1998a) at Serra do Cipó. These authors found only one individual of B.…”
Section: Resultscontrasting
confidence: 52%
“…They also did not find any evidence for introgression into any of the parental species. Borba & Semir (1998a) depicted a series of weak barriers that could constitute a filter system ensuring the rarity of the hybrids and integrity of B. weddellii and B. involutum at Serra do Cipó: 1) the pollinators are the same, but the main pollinator of one species is the secondary of the other; 2) the pollinarium of B. weddellii does not enter on the stigmatic cavity of B. involutum (only the opposite occurs); 3) despite the species being intercompatible, hybrid seeds display low fertility; 4) parental species are sympatric but no syntopic; 5) the hybrid is selfincompatible or sterile and has inefficient pollination system. Similar mechanisms with several individually weak barriers have been observed elsewhere in the Orchidaceae (Romero & Carnevali 1991).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations